Illustrating Tipitip bubblegum comics in Turkey: Transformation, outreach, humour and literacy engagement. Issue 1 (1st June 2018) - Dinç, Betül Gaye; Alaca, Ilgım Veryeri
This work makes an overview of the evolution of Tipitip bubblegum comics in Turkey, studying its impact on society especially on children for more than four decades. Besides its colourful and positive characteristics, Tipitip comics fostered optimism intertwined with wit tailor made for the Turkish audience at the time. Tipitip not only presented accessible visuals for its audience but also introduced rich content ranging from sports to opera, occupations to traffic, transmitting valuable visual information in each illustration. Tipitip, promoted as 'your cheerful friend', was not only a father figure but also an enthusiast, an adventurer and an inventor as he is seen in many roles, from a conductor to a waiter, from a scout to a drummer, which made these comics inclusive and modern. The Tipitip bubblegum comics, similar to their contemporaries, achieved more than just market success; they benefited their audience, especially children, by reaching even small towns and initiating literary engagement.